Penguatan Legalitas dan Digitalisasi Dokumen Usaha Batik Sragen: Strategi Standardisasi Produk dan Akses Pasar Global - Triyono Adi Saputro; Awalia Rina Rahmawati; Diana Setiawati; Wahyu Tri Muhammad Firdaus; Teguh Hartono (Belalek, 2026)
The batik industry in Sragen Regency, particularly those grouped under the Mekar Jaya Joint Business Group (KUB), has great potential to expand into the global market. However, this potential has not yet been optimized due to the weak legal status of the business entities and the lack of digitization of business documents, making it difficult for local batik products to meet the administrative and quality standards required in both national and international trade. This Community Service Activity (PKM) aims to enhance the understanding and capabilities of batik entrepreneurs in managing business legality and digitizing business documents as part of the product standardization strategy. The implementation method includes preparation, execution, and evaluation stages, with a participatory approach consisting of lectures, socialization, interactive discussions, and Q&A sessions. The activity was conducted in Mei to July 2026 and attended by 20 batik business operators who are members of KUB Mekar Jaya, with two resource persons. The results of the activity showed an increase in participants' understanding of the importance of business legality, such as the Business Identification Number (NIB) and product certification, as well as the utilization of digital systems in business document management. Participants also showed a more positive attitude toward the urgency of product standardization as a requirement to penetrate the global market. This activity is expected to be the first step for batik entrepreneurs in Sragen to strengthen their competitiveness, open access to the global market, and serve as a replicable model for other joint business groups in Sragen Regency.